Mass spectrometry analysis of redox forms of High-Mobility Group Box-1 Protein in cerebrospinal fluid: initial experience. - Światły, Agata; Wąsik, Norbert; Hajduk, Joanna; Matuszewska, Eliza; Dereziński, Paweł; Sokół, Bartosz; Jankowski, Roman; Kokot, Zenon; Matysiak, Jan (Journal of Medical Science, 2019)
Introduction. High-mobility group box 1 (HMGB1) is an alarmin with proinflammatory potential determined by redox status of the cysteines at position 23 and 45. It may also play a role as a biomarker in biological fluids. The aim of this study was the identification of different HMGB1 redox forms in cerebrospinal fluid (CSF) obtained from subarachnoid hemorrhage patients. Material and Methods. 6 CSF samples were collected from aneurysmal subarachnoid haemorrhage patients. Commercially available HMGB1 isoforms served as a positive control. Immunoprecipitation and electrophoretic isolation of HMGB1 protein were performed, then both CSF and control were analyzed using mass spectrometry technique. To distinguish between fully reduced (thiol group at C23 and C45) and disulfide (disulfide bond connecting C23 and C45) HMGB1 forms, top-down sequencing of the spectra was performed. Results. Top-down sequencing analysis allowed to distinguish between HMGB1 isoforms only in commercially available standard without preceding immunoprecipitation and electrophoresis. MALDI spectra differ i.e. on the fully reduced HMGB1 spectrum fragmentation occurs before and beyond C22, which is not present on the disulfide HMGB1 spectrum. Analysis of HMGB1 isolated from CSF obtained from subarachnoid hemorrhage patients gave no results. Conclusions. Top-down sequencing enables to distinguish between redox forms of HMGB1. Electrophoresis and tryptic digestion cannot precede mass spectrometry analysis of redox forms of HMGB1 due to the reduction of disulfide bonds during these processes. Preferred method of isolation of HMGB1 for direct analysis using top-down sequencing mustn’t include protein digestion or degradation.